The interest rate pass-through in the euro area during the sovereign debt crisis - Julia von Borstel; Sandra Eickmeier; Leo Krippner (Deutsche Bundesbank, 2015)
We investigate the pass-through of monetary policy to bank lending rates in the euro area during the sovereign debt crisis, in comparison to the pre-crisis period. We make the following contributions. First, we use a factor-augmented vector autoregression, which allows us to assess the responses of a large number of country-specific interest rates and spreads. Second, we analyze the effects of monetary policy on the components of the interest rate pass-through, which reflect banks' funding risk (including sovereign risk) and markups charged by banks over funding costs. Third, we not only consider conventional but also unconventional monetary policy. We find that while the transmission of conventional monetary policy to bank lending rates has not changed with the crisis, the composition of the IP has changed. Specifically, expansionary conventional monetary policy lowered sovereign risk in peripheral countries and longer-term bank funding risk in peripheral and core countries during the crisis, but has been unable to lower banks' markups. This was not, or not as much, the case prior to the crisis. Unconventional monetary policy helped decreasing lending rates, mainly due to large shocks rather than a strong propagation.
Keywords: E5; E43; E44; C3; 330; interest rate pass-through; factor model; sovereign debt crisis; unconventional monetary policy